Sheltie to the rescue - Clover, Peter (New York : Aladdin Paperbacks, 2001)
Emma is glad when her parents agree that Sheltie can come along on the family vacation to the beach and even happier when he helps to rescue another pony from a dangerous situation.
Accelerated Reader AR
Keywords: Shetland pony -- Fiction; Ponies -- Fiction; Vacations -- Fiction